HUBUNGAN ANTARA DUKUNGAN KELUARGA DENGAN KUALITAS HIDUP PADA PASIEN HEMODIALISA DI RUMAHSAKIT LIRA MEDIKA KARAWANG - Tri Fenty Windiarti; Asep Paturohman; Roma Tao Toba Muara Ria (Jurnal Multidisiplin Borobudur, 2023)
The hemodialysis process which takes 3-4 hours has a negative impact, this condition causes a decrease in the patient's quality of life. Family is an influential factor in treatment so as to improve the quality of life of patients. The aim of the study was to determine the relationship between family support and quality of life in hemodialysis patients at Lira Medika Karawang Hospital. Methods: This research is a quantitative research, descriptive correlation method, with a cross-sectional time approach, using a total sampling technique with a total of 35 instrument respondents using a family support questionnaire and WHOQOL-BREEF, data analysis with Chi Square. Results and analysis: the study shows that respondents who have large family support with a high quality of life are quite large (77.8%), while respondents who have small family support with a low quality of life are quite large (72.4%). Obtained p value: 0.001 <a: 0.5 Discussion: so there is a significant relationship between family support and quality of life in hemodialysis patients at Lira Medika Karawang Hospital. The greater the family support, the higher the quality of life of hemodialysis patients.